Unlocking Consumer Choices: The Impact of Halal Labels, Brand Image, Quality, and Price on Buying Decisions - Rahmania, Dea; Fadhlillah, Penny Rahmah (SAN Scientific, 2024)
This research aims to determine whether there is an influence of the Halal Label, Brand Image, Product Quality and Price Perception on Purchase Decisions for Cempaka Putih Mixue Ice Cream and reviews in Islam. The population of this study were consumers who had purchased Mixue Ice Cream at the Cempaka Putih branch at least once, with a total of 100 respondents. The sampling technique uses a non-probability method, with a purposive sampling technique through distributing questionnaires. The research results show that the halal label has no influence on purchasing decisions, brand image influences purchasing decisions, product quality influences purchasing decisions, price perception influences purchasing decisions. Managerial Implications The findings of this research indicate that factors such as halal labels, brand image, product quality, and price perceptions play an important role in influencing consumer purchasing decisions. For company managers, especially those operating in markets where most consumers are Muslim, this emphasizes the importance of ensuring products have clear and reliable halal certification, because this can increase customer trust and loyalty. This paper contributes to understanding the dynamics of food product purchasing decisions in Muslim markets and provides practical insights for companies to increase their competitiveness.